Effect of Endophyte Infection and Clipping Treatment on Resistance and Tolerance of Achnatherum sibiricum - Qin, Junhua; Gao, Yuan; Liu, Hui; Zhou, Yong; Ren, Anzhi; Gao, Yubao (Frontiers in Microbiology, 2016)
It is well-documented that endophytes can enhance the resistance of agronomical grasses, such as tall fescue and perennial ryegrass to herbivory. For native grasses, however, the related reports are limited, and the conclusions are variable. Achnatherum sibiricum is a grass native to the Inner Mongolian steppe. This grass is highly infected by endophytes but does not produce detectable endophyte-related alkaloids known under normal conditions. In this study, the contributions of endophytes to the resistance of A. sibiricum to Locusta migratoria were studied. We found that locusts preferred EF (endophyte-free) plants to EI (endophyte-infected) plants, and the weight of locusts fed on EI plants was significantly lower than those fed on EF plants. Hence, endophyte infection significantly enhanced the resistance of the host to L. migratoria. Endophyte infection significantly decreased the concentration of soluble sugar and amino acids while significantly increasing the concentration of total phenolic content, and these metabolites may contribute to herbivore resistance of the host. The clipping treatment further strengthened the locust resistance advantage of EI over EF plants. After clipping, the weight of the locusts fed on EI plants significantly decreased compared with those fed on unclipped plants, whereas the weight of the locusts fed on EF plants increased significantly. The results suggested that endophyte infection could increase herbivore resistance while decreasing the tolerance of the host grass by mechanisms apart from endophyte-conferred alkaloid defense.